How do you solve the following system using elimination!

2x-3y=61

2x+y=-7

Printable View

- February 2nd 2009, 02:13 PMamberkraidichSolving Systems Using Elimination
How do you solve the following system using elimination!

2x-3y=61

2x+y=-7 - February 2nd 2009, 07:21 PMRapha
Good day to you

E is supposed to mean equation

(E1) 2x-3y=61

(E2) 2x+y=-7

Comparing E1 with E2 you see they both have '+2x' in it. Thus we calculate (E1) - (E2) and you get

2x-3y - [2x+y]=61 - [-7]

More calculating

2x - 3y - 2x -y = 61 + 7

2x - 2x -3y - y = 68

-3y - y = 68

-4y = 68

y = - 17

how to get x? Use y = - 17 in (E1) for example, then

(E1) 2x-3*(-17)=61

2x + 51 = 61

2x = 10

x = 5

Okay?

Cheers,

Rapha